Gestión del cuidado de enfermería en los servicios de salud hospitalarios - Gutiérrez Méndez, Norma Caridad (2007)
This study refers to a descriptive-qualitative research having conceptions and practice of manager nurses in a Hospital setting as a caring agency objective .The purpose is to revalue caring agency concept as well as to provide useful theoretical contribution to practice in health institution and academic setting, regarding conceptions and approaches to caring agency exercise starting from theoretical bases given by Leonardo Boff, Edgar Morin, Vera Regina Waldow, Suzanne Kérouac for caring and agency. It corresponds to a organizational area. It has a direct relationship to caring investigation line according to present curriculum from nursing doctorate program of Postdegree school-National University of Trujillo. Data were collected by a semi-structuctural interview to nurses with manager charge in hospital services from hospitals: Belen of Trujillo, Regional Docente and Victor Lazarte Ehegaray, categories such as reflexions over conceptions of caring agency in Hospital health services and caring agency practice, were emerged from the analysis . Results allowed us to understand that caring agency is conceived as a multi-dimensional an complex process envolving simultanity in agency and caring with singularities of autonomy, dependence, unidual actions of routine creativity, being necessary a disciplinary- interdisciplinary articulation, as well as singulars spaces for agency acting where resonant and dissonant features of caring agency occur. As study outcome, a conceptual model for caring agency useful for practicing, professional education and researching, is proposed, providing typical essential elements to nursing caring and agency.